Solar radiation effect on the complexation capacity of aquatic humic substances with metals - Melo,Camila A. (2012)
This study had as main objective to assess the effect of solar radiation on the capacity of the aquatic humic substances (AHS) to complex Al3+, Cr3+, CrO4(2-) and Ni2+. Microcosms were prepared with AHS from Preto River containing 5.0 mg L-1 of dissolved organic carbon and different concentrations of metal species, being exposed to solar radiation, in situ. Conditional stability constants obtained for the AHS-Cr3+, AHS-Ni2+ and AHS-CrO4(2-) complexes were 2.0 × 10-2, 1.1 × 10-5 and 2.6 × 10-2, respectively. The results showed that solar radiation is responsible for decreasing capacity complexation in 15-26% for AHS-Al3+, 15-72% for AHS-Cr3+, 12-18% for AHS-CrO4(2-) and 13-42% for AHS-Ni2+. We can conclude that solar radiation alters metals' availability previously complexed to AHS, making them available in the aquatic body.